Role of interleukins in dermatology: Exploring the immune mechanisms in skin diseases - Alvaro Prados‐Carmona; Francisco J. Navarro‐Triviño; Ricardo Ruiz‐Villaverde; Alfredo Corell (Wiley, 2024)
Abstract Interleukins are central in the modulation of immune responses. This narrative review aims to summarize the growing evidence on their significance as key drivers of numerous cutaneous diseases with a special focus in some of the more prevalent chronic inflammatory dermatologic diseases such as psoriasis, atopic dermatitis, allergic contact dermatitis, urticaria, and hidradenitis suppurativa. Additionally, we discuss their relevance in the recent developments in targeted therapies that have significantly transformed the management of these skin conditions. To this end, we have conducted a comprehensive search through the Cochrane Library and Database of Systematic Reviews and the MEDLINE search engine, and we have summarized the available clinical evidence considering up to 466 records including meta‐analyses, systematic reviews, reviews and clinical trials. Ultimately, this review intents to foster both dermatologist and non‐dermatologist physicians' understanding of the immunology behind the clinical manifestations of some of the most common inflammatory skin diseases and engage with the novel therapeutic approaches by providing accessible insights into the implications of interleukin pathways dysregulation.